(untitled) (Research, Society and Development, 2022)
Objective: To analyze how Environmental Education has been conceived by pedagogy students during the teaching education process and has as its background the philosophical basis of Being and Making "EcoActive" together with the contributions of dialectical hermeneutic nature of Habermas’ Critical Theory of Communicative Action. Methodology: This is research of qualitative, basic, field, exploratory approach and dialectical hermeneutic method, using the moments of Habermas (2000): descriptive, comprehensive and interpretative. An open question questionnaire was used, applied to students of the pedagogy course attending the optional environmental education course of the 8th semester. After the analysis of the questionnaires, habermasian hermeneutic interpretation was made about the light of the Theory of Communicative Action. Results: It was observed that most of the participating students have a romantic/naturalistic conception of environmental education, with emphasis on conservationist and preservationist concepts, making it clear that they have a knowledge directed to nature and people, a fragmented and reduced knowledge, which lacks greater explanations, understandings for solid knowledge constructions in the formation of critical and reflective subjects. Final considerations: It becomes interesting to think of Habermas as an important part in the integration of environmental care, since his discourse directs us to legality, veracity and communicative freedom.